Folklore as the Key to Instilling Ethical Values in Javanese Language Learning - Balqis Fauzatul Rohmah; Choirul Anam (Tarsib: Jurnal Program Studi PGMI, 2025)
Folklore is part of the cultural heritage created by humans and inherited from generation to generation, both orally and partially oral. In the context of education, especially in the digital era full of global information flows, folklore plays an important role in maintaining local values and the character of the nation. Culture cannot be separated from the education received, because education is a means to transfer cultural values to the younger generation. Javanese folklore, which has valuable moral, ethical, and character values, is very useful in the process of learning Javanese language in instilling ethical values. Teaching materials using folklore will shape students’ attitudes to be polite, cultured, and noble and become a pattern of regional cultural conservation and a filter against foreign cultures that are not in accordance with the personality of the nation. The method presented in this study uses a literature study with qualitative descriptiveness. The data used is secondary data such as books, journals, documents, and other publications. Data analysis was carried out in three stages, namely organize, synthesize, and identify. Through folklore, noble values can be instilled in the souls of students as part of character education. Learning Javanese language at the elementary school level not only teaches language and literature, but also shapes students’ personalities to behave according to Javanese culture that is polite and noble.